2021
DOI: 10.1371/journal.pone.0247794
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of COVID-19 incidence and the sociodemographic context in Brazil

Abstract: Background Identified in December 2019 in the city of Wuhan, China, the outbreak of COVID-19 spread throughout the world and its impacts affect different populations differently, where countries with high levels of social and economic inequality such as Brazil gain prominence, for understanding of the vulnerability factors associated with the disease. Given this scenario, in the absence of a vaccine or safe and effective antiviral treatment for COVID-19, nonpharmacological measures are essential for prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 18 publications
1
50
0
7
Order By: Relevance
“…Individuals living in higher HDI areas may have access to tests through private laboratories and clinics (less prone to shortage in testing). Despite universal susceptibility to COVID-19, populations with increased social vulnerability in Brazil are more and unequally affected by COVID-19, 35 indicating that policies to prioritize low income individuals need to be considered and urgently implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals living in higher HDI areas may have access to tests through private laboratories and clinics (less prone to shortage in testing). Despite universal susceptibility to COVID-19, populations with increased social vulnerability in Brazil are more and unequally affected by COVID-19, 35 indicating that policies to prioritize low income individuals need to be considered and urgently implemented.…”
Section: Discussionmentioning
confidence: 99%
“…The study period was February 25 to September 26,2020 using the ordinary least squares (OLS), spatial autoregressive model (SAR), and conditional autoregressive model (CAR) and the local regression model called multiscale geographically weighted regression (MGWR). The MGWR model fit improved when compared to the OLS, SAR and CAR 5 .…”
Section: Introductionmentioning
confidence: 93%
“…Raymundo et al 5 , reported that the MGWR model was the most suited model in comparison of OLS (CCM) model in the study of spatial analysis of COVID-19 incidence and the sociodemographic context in Brazil.…”
Section: Constant Coefficient Model(panel Ols)mentioning
confidence: 99%
“…This pandemic promoted uneven impact on health of populations, among countries and regions [1] , with the severity and mortality being higher in poorer communities. Educational, economic, social, and other negative impacts are more significant in least developed societies, as recently showed in Brazil [ 2 , 3 ]. A global deployment, allocation, followed by local rollout in scale, are dimensions to be tackled aiming at achieving global control of Covid-19.…”
mentioning
confidence: 93%